Flavor Stability And Volatile Compound Preservation In Pre-Workout, Post-Workout, And Meal-Replacement Formulas - Aakash J Dadhania (Revista Electronica de Veterinaria, 2024)
The stability of flavor and aroma compounds is a critical determinant of product quality, consumer acceptance, and market success in sports nutrition formulations. This study inves- tigates the mechanisms of volatile compound degradation and preservation in pre-workout, post-workout, and meal-replacement products under controlled environmental and processing conditions. A comprehensive experimental dataset was developed comprising formulation parameters, GC–MS and HS-SPME profiles, and sensory evaluation data. The formula- tions—caffeine–citrus (pre-workout), chocolate–vanilla whey (post-workout), and fruit–nut blends (meal-replacement)—were subjected to accelerated storage conditions at varying tem- peratures (25°C–80°C), relative humidity levels (50–70%), and durations (7–30 days). Quan- titative analysis using Gas Chromatography–Mass Spectrometry revealed significant declines in key volatiles such as limonene, hexanal, and vanillin, corresponding with sensory score reductions over time. Principal Component Analysis (PCA) and first-order kinetic modeling were applied to interpret degradation pathways and to identify influential parameters governing flavor loss. Results indicate that microencapsulation with maltodextrin or gum arabic, com- bined with antioxidant inclusion (ascorbic acid or tocopherols), significantly enhanced volatile retention by 25–40% compared to untreated controls. The findings demonstrate a strong correlation (r > 0.85) between chemical and sensory data, validating the analytical framework. This study establishes a reproducible, multi-modal dataset integrating chemical, sensory, and computational evidence, offering a robust methodology for optimizing flavor stability and preservation strategies across diverse sports nutrition formulations.